2014
DOI: 10.1108/jeim-06-2013-0029
|View full text |Cite
|
Sign up to set email alerts
|

A survey on recent research in business intelligence

Abstract: Purpose-Business intelligence (BI) has been applied in various domains to take better decisions and it provides different level of information to its stakeholders according to the information needs. The purpose of this paper is to present a literature review on recent works in BI. The two principal aims in this survey are to identify areas lacking in recent research, thereby offering potential opportunities for investigation. Design/methodology/approach-To simplify the study on BI literature, it is segregated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 45 publications
(30 reference statements)
1
60
0
9
Order By: Relevance
“…In spite of all these, currently, many studies on BI have focused on its applications developmentas shown in the study by (Aruldoss, Lakshmi & Prasanna Venkatesan, 2014) about "A survey on recent research in business intelligence". Côrte-Real, Ruivo & Oliveira (2014) emphasized this in their research about "The diffusion stages of business intelligence & analytics (BI&A): A systematic mapping study", where they surveyed a total of 30 articles from 11 journals and 8 conferences through a review of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of all these, currently, many studies on BI have focused on its applications developmentas shown in the study by (Aruldoss, Lakshmi & Prasanna Venkatesan, 2014) about "A survey on recent research in business intelligence". Côrte-Real, Ruivo & Oliveira (2014) emphasized this in their research about "The diffusion stages of business intelligence & analytics (BI&A): A systematic mapping study", where they surveyed a total of 30 articles from 11 journals and 8 conferences through a review of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…BI helps to portray the organization's information assets in order to yield an accurate understanding of the associated business dynamics. This leverages the making of better decisions by improving the information gathered from multiple sources and its subsequent processing (Aruldoss, Lakshmi Travis, & Prasanna Venkatesan, 2014). BI has been growing exponentially in relevance and importance in the last three decades, as the amount of specialized literature published in the last few years reflects, addressing in particular the different BI categories (artificial intelligence; benefits; decisions; implementation; and strategies) and the main research strategies (Jourdan, Rainer, & Marshall, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, BI has been implemented in many fields to give input to the decision-making for example, E-learning, financial, higher education, strategy making, and other areas. BI can integrate the data from all levels to give the right information at the right time [7]. According to Sharda [2], BI applications can be divided into three kinds of applications: strategic, tactical and operational applications.…”
Section: Bi Applicationsmentioning
confidence: 99%
“…OLAP comes in four types or styles, the relational OLAP or ROLAP, multidimensional OLAP, otherwise known as MOLAP, HOLAP for Hybrid Online Analytical Processing, and desktop OLAP. OLAP and ROLAP both allow analysis of data by using relational or multidimensional data model, but there are a few key differences [2], [7].…”
Section: Olapmentioning
confidence: 99%